1898-99 Ala. Laws 1046 - (:unkn) unknown (My University, 1899)
Granted the town the authority to regulate, tax, and license dealers in Pistols, pistol cartridges, Bowie knives, and dirk knives. Licenses shall not exceed fifty dollars.
Keywords: TAX - DEALERS